Hybrid Hydrogels Based on Poly(vinyl alcohol) (PVA)/Agar/Poly(ethylene glycol) (PEG) Prepared by High Energy Electron Beam Irradiation: Investigation of Physico‐Mechanical and Rheological Properties. Issue 2 (4th November 2016) - Entezam, Mehdi; Daneshian, Hanieh; Nasirizadeh, Navid; Khonakdar, Hossein Ali; Jafari, Seyed Hassan
Abstract : PVA/agar/PEG hybrid hydrogels for wound dressing applications are prepared by an EB irradiation method. The effects of agar and PEG on their physico‐mechanical and rheological properties are systematically investigated. A theoretical analysis of swelling kinetics reveals that the swelling mechanism is under the influence of both agar and PEG contents. The rheological behavior of the hydrogels shows a strong dependency on PEG content. Abstract : A series of hybrid hydrogels based on poly(vinyl alcohol) (PVA)/agar/poly(ethylene glycol) (PEG) prepared by a solution casting method using e‐beam irradiation are investigated to determine the effect of agar and PEG content (1, 2, and 4 wt%) on their physicomechanical and rheological properties. The gel content of the hydrogels decreases with increasing agar and PEG contents. The equilibrium swelling of PVA hydrogel decreases on blending with agar while adding PEG to PVA/agar increases the swelling by about 400%. No obvious change in the dehydration behavior of the hybrid hydrogels is observed on changing agar and PEG contents. The solid‐like rheological behavior of the hydrogels is not significantly affected by agar content, while it approaches a liquid‐like behavior at high PEG loading. The tensile strength of the hybrid hydrogels is improved by increasing agar content, while its elongation‐at‐break is decreased. On the other hand, the opposite results are found regarding the influence of PEG and its content on the mechanical properties of the hybrid hydrogels.